Entretiens (1998-2001) - Lebert, Marie (Salt Lake City, UT : Project Gutenberg, 2008)
"Entretiens (1998-2001)" by Marie Lebert is a collection of interviews focused on digital culture and its evolution, likely written in the early 21st century. The book gathers insights from various professionals in the literary and digital fields, including librarians, authors, editors, and researchers, exploring their perspectives on the internet, electronic publishing, copyright issues, and the future of media. The opening of the collection presents a diverse range of contributors, each sharing their experiences and viewpoints on the changing landscape of publishing and communication in the digital age. For instance, Nicolas Ancion discusses his role in digital publishing and the imaginative challenges it poses for future editors, while Alex Andrachmes reflects on the unique writing style fostered by the internet, emphasizing the new narrative possibilities it offers. The conversations reflect on themes such as the balance between traditional print and electronic media, the implications of e-books, and the societal shifts driven by the information age, setting the stage for a broad discussion of how digital advancements are reshaping literature and culture. (This is an automatically generated summary.)
Release date is 2008-10-26
Produced by Al Haines
Keywords: Internet; World Wide Web